Physical development and physical preparedness of young karatists’ status on the stage of base pre-treatment - Галімський, В. А.; Ровний, А. С. (Slobozhanskyi Herald of Science and Sport, 2011)
In the article physical development and physical preparedness of karatists’ status is examined on the stage of base pre-treatment. Establishing a cross-correlation connection between the separate indexes of physical development and physical qualities determines the prospect of development of necessary qualities based on which the technique of shock motions is formed in a karate.